Laparoscopic Evaluation of Tubal Factors in Female Subfertility - Muhammad Awais Khalid, Nida Khurshid, Asma Yasin, Madiha Afzal, Uzma Aziz, Samar Hussain (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The objective of this study was to evaluate frequency of tubal factors as a cause of female subfertility using laparoscopy. Study design: It was a cross-sectional study Setting: This study was conducted at Obstetrics and Gynecology department, Arif Memorial Teaching Hospital Lahore / Rashid Latif Medical College Duration of study: Study was done in 6 months [June 4, 2022 till December 4, 2022] Methodology: Using non probability consecutive sampling 179 females with primary and secondary subfertility who fulfilled the inclusion and exclusion criteria were enrolled in the study. Detailed demographics were recorded after taking informed written consent. Results: The mean age of participants was 29.12 ± 4.04 years with minimum and maximum age between 19 and 42 years. The mean duration of marriage was 7.13 ± 3.66 years with minimum and maximum duration of marriage between 3 and 17 years. The mean duration of subfertility was 5.32 ± 3.26 years with minimum and maximum duration of subfertility between 2 and 18 years. There were 137(76.5%) of the cases who had primary and 42(23.5%) females had secondary subfertility. A total of 56(31.2%) females had tubal factors and 123(68.7%) females did not have tubal factors as cause of subfertility. There were 39(21.8%) females who had Peri tubal adhesion, 17(9.5%) females had tubo ovarian mass. Among the 56 participants who had tubal factor presents 40 (22.3%) had bilateral blocked tubes Conclusion: Through the findings of this study , we concluded that 31.2% females had tubal factors subfertility, including 21.8% females with peri tubal adhesion and 9.5% females with tubo ovarian mass. 22.3% of the participants had bilateral blocked tubes. Hence proper evaluation of the female partner in a subfertile couple should be done by laparoscopy which is a superior tool for diagnosing tubal factors responsible for subfertility and tubal patency should also be confirmed before prescribing treatment such as ovulation induction. Keywords: Infertility, diagnostic laparoscopy, tubal factors, peri tubal adhesion, tubo ovarian mass, blocked tubes